IMPLEMENTASI AKAD MUKHABARAH DALAM MENINGKATKAN PRODUKSI PADI: STUDI KASUS DI KAMPUNG BARU, DESA KERTAMUKTI, KECAMATAN CIPATAT - Rohmat, Dede Saepul; Tunggara, Imam (Jurnal Pelita Nusa, 2024)
Akad Mukhabarah is a collaboration between landowners and cultivators, where landowners provide land to be planted and maintained by farmers with a mutually agreed share of the proceeds. In Kampung Baru, Kertamukti Village, this rice field cultivation cooperation is known as "maro". This research focuses on the implementation of mukhabarah contracts by rice farmers, with two main questions: 1) What is the mechanism for the implementation of mukhabarah contracts for rice farmers in Kampung Baru, Kertamukti Village? 2) What is the impact of the implementation of the mukhabarah contract for both parties in Kampung Baru, Kertamukti Village? This research is qualitative and descriptive with data collection methods through interviews, observations, documentation studies, and data analysis. The results of the study show that the cooperation in the management of rice fields in Kampung Baru is similar to the concept of mukhabarah, but it does not fully follow Islamic teachings because the limits in land management are not set at the time of the contract. As a result, there is an imbalance between landowners and managers, because agreements are only made orally without written documents. The distribution of proceeds is carried out based on an agreement between landowners and farmers. The mukhabarah cooperation provides good economic opportunities for rice farmers in Kampung Baru, Kertamukti Village.